PENDEKATAN MULTIKULTURAL DALAM PENDIDIKAN AGAMA DI MADRASAH - Jauhari, Ahmad; Suwendi , Suwendi (Penerbit Lafadz Jaya, 2025)
This research aims to analyze the Multicultural Approach in Islamic Religious Education in Madrasahs. The method used is descriptive qualitative. This research conducts an in-depth review of various sources such as reference books, scientific journal articles, educational policy documents, and relevant research reports. The study results indicate that there are efforts to implement a multicultural approach in madrasahs, which is integrated into various learning activities. The goal of this effort is to foster attitudes of tolerance and respect for diversity, whether in terms of religion, culture, ethnicity, and so on. However, in practice, the implementation is not as easy as it is imagined in theory. There are obstacles, such as the lack of in-depth understanding of the multicultural approach among educators and students. The proposed solution is to implement education and training for educators so that they can master the techniques of conducting lessons with a multicultural approach effectively. Related to this approach, there have been several previous studies examining its implementation in schools with highly heterogeneous students. Unlike this study, which focuses on implementation in madrasahs, where students are generally homogeneous, especially in terms of religion. The findings of this research emphasize the importance of applying a multicultural approach in madrasahs to create a more inclusive and tolerant learning environment.